A Transylvanian Physician and Politician: Dr. Nicolae Stoia (1830-1879) - Onojescu, Alexandru (Medicine and Pharmacy Reports, 2014)
Our research aims at recovering the biography of one name within the historical list of the Romanian physicians from Transylvania: Dr. Nicolae Stoia. At the beginning of the second half of the 19 th century he was a well-known figure among his co-nationals – chief-physician of the Răşinari borough and later chief-physician of the Greek- Catholic Metropolitan See of Blaj, member of the political and national elite, Dr. Stoia passed away suddenly, before he reached 50, without leaving behind many documentary traces. His years of study at the University of Vienna, his good relations with some of his professors and the years of practice in this city’s hospitals could have given him the opportunity of a career in the Empire’s capital. Instead, he had chosen to return to Transylvania in 1861, in order to take part in the political enthusiasm generated by the new liberal regime. During the next two decades, Dr. Stoia was present at many of the important political actions of the Romanians from Transylvania, in the meanwhile fulfilling his professional duty as a physician in Răşinari and Blaj, until 1878 when he was forced to retire to Vienna for medical treatment. Sadly, the evolution of his illness was very fast and led to his death within less than a year.